Pengaruh Model Pembelajaran Hibrid Terhadap Kemampuan Komunikasi Matematika Pada Sekolah Menengah Pertama Negeri 1 Curup Tengah - Bainamus , Putri Milanda; Hartanto; Abdullah, M. Ilham (Mathematics Education Journal, 2017)
This research aims to determine the influence of hybrid learning model to communication mathematics junior high school students. This research is a quantitative with experimental methods in the form of pure experiment types. The population were all eighth grade students at Public Junior High School 1 of Middle Curup, Rejang Lebong Regency, Bengkulu Province in 2015/2016. The number of samples uses 37 persons as experimental class and 35 persons as control class. This research is a pure experiment using a pretest-posttest control group. In this study, the data collection method used is the testing techniques. Based on the analysis can be concluded that there is a significant effect on communications hybrid learning model mathematics junior high school student.